2003
DOI: 10.1590/s0037-86822003000300006
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos epidemiológicos e clínicos do escorpionismo na região de Santarém, Estado do Pará, Brasil

Abstract: This is a descriptive and prospective study on epidemiological and clinical aspects of 72 scorpion accidents admitted to Santarém Municipal Hospital, state of Pará, Brazil, from February 2000 to February 2001. Only 8.3% brought the animal with them, identified as T. cambridgei. The majority of victims were male (83.3%). The mean age and the time of the medical help were respectively 33.6±18.3 years and 4.6±3.2 hours. The parts of the body most affected were the superior members (51.5%). Local symptoms occurred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
57
0
30

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(99 citation statements)
references
References 8 publications
12
57
0
30
Order By: Relevance
“…The most common symptoms reported were localized pain, edema, hyperemia, swelling, burning, numbness and itching, and the systemic symptoms were a dry mouth, thirst, sweating, hypotension, hypertension, cramps and shivering, nausea, vomiting, difficulty in breathing, tachycardia, sialorrhoea, restlessness, hemolyticuremic syndrome, cyanosis, cardiac failure and/or acute pulmonary edema and death 3,6,7,10,23,24,27,28,31,36 . Scorpion stings can cause similar clinic manifestations in many countries of Central and South America, North Africa, the Middle East and Asia 5,9,13,21,30,37,38 . In our study, the most common symptoms reported were: localized pain (47.58%), hyperemia (24.14%), edema (23.45%) and numbness (6.21%).…”
Section: Discussionmentioning
confidence: 99%
“…The most common symptoms reported were localized pain, edema, hyperemia, swelling, burning, numbness and itching, and the systemic symptoms were a dry mouth, thirst, sweating, hypotension, hypertension, cramps and shivering, nausea, vomiting, difficulty in breathing, tachycardia, sialorrhoea, restlessness, hemolyticuremic syndrome, cyanosis, cardiac failure and/or acute pulmonary edema and death 3,6,7,10,23,24,27,28,31,36 . Scorpion stings can cause similar clinic manifestations in many countries of Central and South America, North Africa, the Middle East and Asia 5,9,13,21,30,37,38 . In our study, the most common symptoms reported were: localized pain (47.58%), hyperemia (24.14%), edema (23.45%) and numbness (6.21%).…”
Section: Discussionmentioning
confidence: 99%
“…Among these, the most important species are T. serrulatus, T. bahiensis, T. stigmurus and T. trivittatus in South America; (2,8,33,36); C. suffusus, C.…”
Section: Introductionmentioning
confidence: 99%
“…Entre as várias manifestações neurológicas registradas após picadas de escorpião, existem relatos de dismetria, ataxia de marcha e mioclonias 11 , contraturas musculares 5 8 9 e disartria 9 10 . A pesquisa de tais manifestações na população pediátrica é comprometida pelas características próprias dessa faixa etária.…”
unclassified